Real time high frequency analysis system / Nor Zaheda Zainal - Zainal, Nor Zaheda (2009)
The HF with 3 to 30 MHz spectrum is utilized for long distance communications by the military, amateur radio, shipping and diplomatic services. Communications is no longer limited to voice and telegraphy, but now include applications such as email, text messaging, image, and telemetry. This project looks into the design and development of A Real Time High Frequency Analysis System provides a program to analyze High Frequency (HF) signal. This thesis presents work carried out in developing a user friendly system to observe and analyze HF signal with MATLAB environment. The system consist two main parts; Offline HF analysis and real time (online) HF analysis. In offline mode, user can analyzes the signal by using HF signal in '*.wav' file form. While in online mode, the system requires HF receiver (YAESU VR 5000) to be connected to personal computer and online signal will be observed, recorded and analyzed. This analysis system only capable to read the HF signal data in '*.wav' file (audio file format), in order to access the HF data to be load into the system. Sampling frequency that is used is 8000Hz and the channel bandwidth is 3 kHz. This corresponds to the typical voice bandwidth used in HF communication systems. This system provides a FIR filter to filter the signal in order to observe a smooth result. This system also can determine the modulation type, the frequency contains and the bit rate of the signal by using the periodogram and spectrogram techniques.